2008
DOI: 10.1063/1.2966350
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed organic thin-film transistors with vertical nanophase separation

Abstract: Articles you may be interested inThickness modulation effects of Al2O3 capping layers on device performance for the top-gate thin-film transistors using solution-processed poly(4-vinyl phenol)/Zn-Sn-O gate stacks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
123
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 12 publications
6
123
0
1
Order By: Relevance
“…Although the reason for this dual segregation was not revealed exactly, this structure, as shown in the inset of Figure 7b, provides an excellent charge transport pathway. Figure 7b shows comparative plots for OFETs based on a TIPS-pentacene: PαMS blended film (solid line) and sole-TIPS-pentacene (broken line) [48]. The TIPS-pentacene: PαMS blended film exhibited electrical properties comparable to sole-TIPS-pentacene.…”
Section: Processing Additivementioning
confidence: 99%
“…Although the reason for this dual segregation was not revealed exactly, this structure, as shown in the inset of Figure 7b, provides an excellent charge transport pathway. Figure 7b shows comparative plots for OFETs based on a TIPS-pentacene: PαMS blended film (solid line) and sole-TIPS-pentacene (broken line) [48]. The TIPS-pentacene: PαMS blended film exhibited electrical properties comparable to sole-TIPS-pentacene.…”
Section: Processing Additivementioning
confidence: 99%
“…[26] Ohe et al reported TIPSpentacene accumulation and stratification at both interfaces with poly(α-methyl styrene) (PαMS) in the middle, pointing to the influence of the substrate on the phase separation outcome. [18] The nature of the polymer structure also plays a role in mediating the vertical phase separation. Blending TIPS-pentacene with a semi-crystalline isotactic polystyrene (i-PS) was reported to form stratification with small molecules segregating to the interfaces; [17] whereas semi-crystalline syndiotactic polystyrene (s-PS) was found to inhibit the segregation and crystallization of diF-TESADT.…”
Section: Introductionmentioning
confidence: 99%
“…Although a lot of research has been published on the advances of using printed TIPS-pentacene in which different research groups have built organic field-effect transistors (OFET) with mobility in the saturation regime greater than 1 cm 2 /Vs [5,6], most organic semiconductor (OSC) circuitry is still based on evaporated pentacene due to the reproducibility and homogeneity of the results. This is due to the inherent problem that plagues TIPS-pentacene and other such small molecule semiconductors that the poor control of the phase distribution and morphology leads to a wider disparity in the device-to-device performance [7].…”
Section: Introductionmentioning
confidence: 99%